(untitled) (Al-Mansour Journal, 2022)
The art of steganography is to hiding the secret information inside other information. There are four steganography Medias (video, audio, text and image) which have different containers. The digital image is one of the most popular kind uses in the internet. This paper a comparison among traditional Least Significant Bit (LSB), proposed modified LSB and Discrete Wavelet Transform (DWT) techniques of steganography are made using the MSE and Peak-SNR measures. Also the capacity between cover image and secret message is play effective way to achieve good quality, that will gives good way to choose best cover that is suitable to hide the specific secret message (Text), thereby achieve good result of MSE and PSNR. The experimental work taken different image formats with different size and use different size of secret message. The obtained results show that; the proposed modified LSB is the best in both basic measures MSE and PSNR, where the traditional LSB is the best in measure of capacity and the DWT is the best in measure of security.